Green entrepreneurial orientation on green radical innovation and environmental performance: The role of supply chain learning - Fikri, Muhammad Ali; Anggraini, Sinta Putri; Rahmatullah, Arwin Yafi (Master of Management, Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2026)
This study investigates the influence of green entrepreneurial orientation on green radical innovation and environmental performance, with supply chain learning serving as a mediating variable. A quantitative research approach was employed using a structured questionnaire distributed to 265 employees across four 4-star hotels in Yogyakarta. Analysis was conducted using PLS-SEM. Results show green entrepreneurial orientation positively affects green radical innovation and supply chain learning but does not directly improve environmental performance. Supply chain learning is found to significantly enhance both green radical innovation and environmental performance and mediates the effect of green entrepreneurial orientation on both outcomes. The originality of this study lies in integrating dynamic capability theory and the knowledge-based view to explain the mechanisms through which green entrepreneurial orientation fosters learning and innovation in the hospitality supply chain. Findings contribute theoretically by clarifying the indirect pathways through which green entrepreneurial orientation generates environmental value. Practically, the study highlights that hotel managers should strengthen cross-supply chain learning processes, optimize environmental performance, and accelerate green innovation.